(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Traffic law enforcement involves the actions taken by law enforcement authorities to ensure public compliance with road safety regulations. These laws are intended to reduce accidents, improve traffic flow, and ensure the safety of all road users. This study focuses on the effectiveness of the Traffic Transport Management Division in implementing traffic laws along Sauyo Road in Barangay Sauyo, Quezon City. It also highlights the responsibilities of local barangay officials in managing and regulating traffic within their jurisdiction. A quantitative correlational research design is employed to evaluate the implementation of traffic laws by the Traffic Transport Management Division in Barangay Sauyo. The study involves two respondent groups with a total of 50 participants: 30 barangay officials and 20 community members. Stratified sampling is used to ensure proper representation. Data are gathered through structured survey questionnaires, and the analysis focuses on the perceived effectiveness of traffic law enforcement in terms of implementation, personnel, and knowledge of traffic rules, policies, and procedures. Most respondents were male, aged 18–25, single, at the college level, and had served in their roles for 1 to 3 years. The assessment of the Traffic Transport Management Division’s effectiveness in implementing traffic laws in Barangay Sauyo Road is rated as “Very Effective” in terms of personnel performance, procedural implementation, and awareness of traffic rules. However, one major problem identified was the inefficient use of technology, including underutilized CCTV systems and traffic sensors. Respondents suggested that traffic flow could be improved through coordinated signalization, road network upgrades, and the adoption of more efficient public transport systems. Additional solutions include enhancing pedestrian infrastructure, implementing stricter parking regulations, and adopting intelligent traffic management technologies. The study concludes that while the Traffic Transport Management Division is largely effective in enforcing traffic laws in Barangay Sauyo, further improvements are needed. These include the enhanced use of traffic technologies, community education campaigns to promote responsible driving behavior, and encouragement of alternative transport modes. The researchers recommend an action plan to further strengthen traffic enforcement and improve road safety and mobility in the area.